2020
DOI: 10.3390/agronomy10040570
|View full text |Cite
|
Sign up to set email alerts
|

Less Is More: Lower Sowing Rate of Irrigated Tef (Eragrostis tef) Alters Plant Morphology and Reduces Lodging

Abstract: Tef (Eragrostis tef (Zucc.) Trotter) is a panicle-bearing cereal crop plant, originating from and grown mainly in Ethiopia. Tef yields highly nutritious gluten-free grain as well as high-quality forage, therefore, interest is rising regarding tef cultivation for grain and forage outside Ethiopia. Lodging is a major factor limiting tef quality and yield, with losses estimated at 30%–35% and presumably higher under mechanical harvest. Studies in other cereal crops suggested that lowering plant density would lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In our pot experiment, deeper sowing of tef induced a significant effect on number of internodes, whereas its effects on lodging angle, crown diameter, and crown root diameter fell below the statistical threshold (Table 4). In our previous study, lodging of four genotypes grown in the field under various plant densities was associated with crown diameter, crown root diameter, and crown root number [21]; in the pot experiment, crown diameter and crown root diameter showed similar effects.…”
Section: Effect Of Sowing Depth On Lodging and Related Traitsmentioning
confidence: 68%
See 3 more Smart Citations
“…In our pot experiment, deeper sowing of tef induced a significant effect on number of internodes, whereas its effects on lodging angle, crown diameter, and crown root diameter fell below the statistical threshold (Table 4). In our previous study, lodging of four genotypes grown in the field under various plant densities was associated with crown diameter, crown root diameter, and crown root number [21]; in the pot experiment, crown diameter and crown root diameter showed similar effects.…”
Section: Effect Of Sowing Depth On Lodging and Related Traitsmentioning
confidence: 68%
“…The effect of sowing depth on tef lodging has not been reported in previous studies. Recently, we reported that lower seedling density reduces lodging index [21]. Published studies on tef [20,29] and other cereals [28] have shown an association between lower plant height and reduced lodging.…”
Section: Effect Of Sowing Depth On Lodging and Related Traitsmentioning
confidence: 87%
See 2 more Smart Citations
“…Millets such as tef face several production constraints since they are mostly cultivated in marginal areas with low moisture and limited fertility conditions ( Dosad and Chawla, 2018 ). Inherent characteristics, such as susceptibility to pests and diseases, can cause a significant yield loss ( Assefa et al, 2011 ; Ben-Zeev et al, 2020 ). One of the main reasons for crop loss is pests, which cause an average 15% reduction in grain quality and yield ( Lee et al, 1981 ; Deutsch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%